Points of Economic and Innovative Growth: a Model for Organizing the Effective Functioning of the Region - D. D. Burkaltseva (Модернизация, инновация, развитие)
Abstract Purpose: the main goal of the article is to build a conceptual model for the organization of eﬀective functioning of the points of economic and innovative growth of the region in modern conditions, taking into account regional and municipal limitations of internal and external nature, with the aim of ensuring economic security, eﬀective interaction of subjects of the "business-power" system Taking into account the inﬂuence of institutional factors. Methods: the methodological basis of research in the article is the dialectical method of scientiﬁc cognition, the systemic and institutional approach to studying and building an organization for the eﬀective functioning of the regional economy in order to ensure its economic security from internal and external threats. Results: the existing mechanism of interaction "business and power" is considered. The ﬁnancial stability of economic entities of the Republic of Crimea is determined. The ﬁnancial independence of the regional budget of the Republic of Crimea has been determined. The dynamics of ﬁnancing of the Federal Target Program "Social and Economic Development of the Republic of Crimea and Sevastopol until 2020" has been revealed. The regional and municipal restrictions of internal and external nature, which constitute a threat to social and economic development, are indicated. Points of economic and innovative growth at the present stage and their advantages and stages of technical organization of their implementation have been determined. A conceptual model of building eﬀective interaction between subjects of the "business-power" system is proposed taking into account the inﬂuence of institutional factors. The conceptual model of organization of eﬀective functioning of points of economic and innovative growth of the region, as a territorial socio-economic system, under modern conditions is constructed. Conclusions and Relevance: we propose to deﬁne four strategic tasks in the sphere of regional development: increasing the competitiveness of regions and strengthening their resource potential; Development of human resources; Development of interregional cooperation; Creation of institutional conditions for the development of regions. For eﬀective management of processes and making correct timely decisions, it is necessary to monitor the indicators by creating situational centers in the regions based on the Internet of things and closed blokchain. As preventive measures, it is necessary to create a communication system for direct and feedback to provide software for monitoring ﬁnancial and economic security at the level of an economic entity on-line. This provision is proposed to develop, maintain, monitor, systematically update at the regional and state level for a timely response in the eﬀective targeted use of small and young business ﬁnancing by the state. For eﬀective uninterrupted functioning at the level of business entities, economic entities use the Internet of things. At the same time, an inalienable and important model is the construction of an eﬀective interaction between the subjects of the "business-power" system. Further research should be directed to the systematization of monitoring indicators of ﬁnancial and economic security at the level of an economic entity on-line. Development and implementation of pilot projects on the use of Internet stuﬀ and blokchain in the public sector, their institutional support, their impact on the regional gross product.